Insomnia analysis based on internet of things using electrocardiography and electromyography - Novi Azman; Mohd Khanapi Bin Abd Ghani; S. R. Wicaksono; Barru Kurniawan; Viktor Vekky Ronald Repi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Insomnia is a disorder to start, maintain, and wake up from sleep, has many sufferers in the world. For patients in remote locations who suffer from insomnia, which requires testing, the gold standard performed requires patients to take the time and travel to the health care center. By making alternatives to remote sleep insomnia testing using electrocardiography and electromyography connected to the internet of things can solve the problem of patients' access to treatment. Delivery of patient data to the server is done to make observations from the visualization of patient data in real-time. Furthermore, using artificial neural networks was used to classify EMG, ECG, and combine patient data to determine patients who have Insomnia get resulted in patient classification errors around 0.2% to 2.7%.